Water-Energy-Mining and Sustainable Consumption: Views of South American Strategic Actors - Estenssoro-Saavedra, J; Parker-Gumucio, C; Baigorrotegui-Baigorrotegui, G (Palgrave Macmillan, 2016)
Mining activity has undeniable environmental impacts due to the nature of its operations, processing plants and foundries. Mining companies proclaim their environmental responsibility by implementing policies that limit environmental risk and impact, while also applying new technologies and production processes that are more respectful of the environment. The degree of efficacy of these sustainability measures and the degree to which companies voluntarily ensure environmental care cannot belie the fact that - No matter what - mining activity has and will always have environmental impacts. There are two major points of view about the subject, according to Whitmore (2006). On the one hand, there are the views of companies - that is to say, the actors who control the mining bulldozers and claim to ensure that everything goes well and that mining is, or can be, sustainable. On the other hand, there are the views of those who are affected by mining activity, such as the communities, peasants and indigenous peoples who are displaced without proper consultation, who suffer illnesses, and whose lifestyles, health and environment are impacted. © Fábio de Castro, Barbara Hogenboom and Michiel Baud 2016, Respective authors 2016 and Eduardo Silva 2016.